Rearing of Pseudacteon spp (Dipt, Phoridae), parasitoids of fire ants (Solenopsis spp) (Hym, Formicidae) - Pesquero, M. A.; Porter, S. D.; Fowler, H. G.; Campiolo, S. (Blackwell Wissenschafts Verlag Gmbh, 1995)
After exposure of Solenopsis saevissima colonies maintained in plastic trays to phorid attack in the field, and subsequent transfer of colonies to covered plastic buckets, we confirmed that P. wasmanni and P. litoralis are indeed parasitoids of fire ant workers. The period from attack to emergence of phorid adults ranged from 35 to 46 days. Adult phorids were maintained live in glass vials with sugar water as a food source for 5 days. These results indicate that Pseudaceton can be reared for biological control release programs with minimal difficulty. Furthermore, parasitized workers could be easily transferred from South America to quarantine laboratories within the egg to adult emergence time period.